Maternal and Neonatal Outcomes With Early Compared With Delayed Pushing Among Nulliparous Women. Issue 2 (June 2017) - Yee, L.M.; Sandoval, G.; Bailit, J.; Reddy, U.M.; Wapner, R.J.; Varner, M.W.; Caritis, S.N.; Prasad, M.; Tita, A.T.; Saade, G.; Sorokin, Y.; Rouse, D.J.; et al.
Abstract : ( Obstet Gynecol. 2016;128(5):1039–1047) Delayed pushing, also known as "laboring down" or "passive descent, " is the practice of resting in the second stage of labor before initiating active bearing down. Some data suggest that delayed pushing may reduce maternal exhaustion, cesarean delivery, severe perineal lacerations, and even increase the likelihood of spontaneous vaginal delivery. However, many studies have reported contradicting results. The authors of the present study hypothesized that delayed pushing is associated with adverse perinatal outcomes and evaluated patient and hospital-level factors of delayed pushing and its association with perinatal outcomes.